Employment mobility and labour market flexibility in the EU - Vassilis Monastiriotis; Stylianos Sakkas (London School of Economics and Political Science (LSE), European Institute, 2021)
Does employment flexibility facilitate cross-regional adjustments via labour mobility? Or is it instead a hinderance to cross-regional equilibration in the labour market? We examine this, drawing on a sample of 11 European countries belonging to different 'varieties' of European capitalism. We identify two opposing potential effects of employment flexibility on outmigration (a negative necessitating effect and a positive facilitating effect) and provide original evidence on the ways in which employment flexibility impacts of the responsiveness of inter-regional outmigration to regional unemployment. We find that employment flexibility is at large associated with less cross-regional adjustability. This is especially so for numerical aspects of flexibility (non-standard forms of employment contracts) and more true for countries in the European south and Scandinavia; while for internal aspects of employment flexibility (irregular hours and patterns of work), as well as for countries of the Continental 'variety' (coordinated market economies), employment flexibility appears to be more synergetic to cross-regional adjustability (via outmigration). We draw implications for our understanding of cross-regional equilibration and for labour market and wider EU policies.
Keywords: R11; R23; J08; J61; 330; Employment flexibility; regional migration; labour market adjustment